The European Union structural assistance audit planning - Lakis, Vaclovas; Simonaitytė, Živilė (Planowanie audytu pomocy strukturalnej Unii Europejskiej, 2011)
Planning is one of the most important and responsible activities in auditing process. The results of an audit, to a large extent, depend on the quality of audit planning. However, the European Union regulations do not provide details on the audit planning of European Union structural assistance and there is a lack of studies on this issue. There is no consensus on the elements of planning: strategy, the structure of an audit plan, and methods are not satisfactory described, not described at all, or identified differently
Ekonomia = Economics, 2011, Nr 2 (14), s. 114-122
Keywords: structural support; audit authority; audit planning